Case Report on the Use of the Waldon Approach on an Adult with Severe to Moderate Intellectual Disability with Autistic Tendencies - Solomon, Walter G.; Greenbaum, Eran (Frontiers in Public Health, 2016)
This clinical case report describes a patient diagnosed with severe to moderate intellectual disability with autistic tendencies, resident in a home for adults with a range of disabilities. She had been resident for 18 years prior to intervention by the author when she was 48 years of age. The author worked with her from June 25th 2013 until January 12th 2015 for a total of 55 Waldon Approach1, movement based lessons each of about 45 minutes of which 33 were documented by video. This report describes changes in her cognition and her social behaviour at a time when there were no other changes in her life. As far as the author is aware this is the first clinical case report on the Waldon Approach to appear in a peer reviewed journal and is unique in that most of the work using the approach is with children who are usually receiving other therapies at the same time as their Waldon Lessons, making it harder to evaluate the attribution of change. During the period of this report she received no other therapy or intervention beyond that provided at Maon Roglit which itself had not changed during this period. The patient remains without speech but there has been real, meaningful and noticeable change in her life from which she appears to derive pleasure. There has been a significant improvement in the patient’s group participation, facial expression and general demeanour.